Swift coalescence of supermassive black holes in cosmological mergers of massive galaxies - Khan, Fazeel Mahmood; Berczik, Peter; Just, Andreas (The astrophysical journal, 2016)
Supermassive black holes (SMBHs) are ubiquitous in galaxies with a sizable mass. It is expected that a pair of SMBHs originally in the nuclei of two merging galaxies would form a binary and eventually coalesce via a burst of gravitational waves. So far, theoretical models and simulations, focusing only on limited phases of the orbital decay of SMBHs under idealized conditions of the galaxy hosts, have been unable to directly predict the SMBH merger timescale from ab-initio galaxy formation theory. The predicted SMBH merger timescales are long, of order Gyrs, which could be problematic for future gravitational wave (GW) searches. Here, we present the first multi-scale ΛCDM cosmological simulation that follows the orbital decay of a pair of SMBHs in a merger of two typical massive galaxies at ##IMG## [http://ej.iop.org/images/0004-637X/828/2/73/apjaa3801ieqn1.gif] $z\sim 3$ , all the way to the final coalescence driven by GW emission. The two SMBHs, with masses ##IMG## [http://ej.iop.org/images/0004-637X/828/2/73/apjaa3801ieqn2.gif] $\sim 10^8$ ##IMG## [http://ej.iop.org/images/0004-637X/828/2/73/apjaa3801ieqn3.gif] $M_ødot $ , settle quickly in the nucleus of the merger remnant. The remnant is triaxial and extremely dense due to the dissipative nature of the merger and the intrinsic compactness of galaxies at high redshift. Such properties naturally allow a very efficient hardening of the SMBH binary. The SMBH merger occurs in only ∼10 Myr after the galactic cores have merged, which is two orders of magnitude smaller than the Hubble time.